A Lib Dem Perspective on Centre‐Left Politics Post‐2015. Issue 1 (19th January 2017) - Cable, Vince
Abstract: This article analyses the political crisis faced by the centre‐left, not just in the UK but throughout the Western world, with few exceptions (Canada). The Liberal Democrat party has been a victim of that crisis, though there are encouraging signs of recovery and there is scope for a wider realignment on the centre‐left.